Cáncer hereditario: fundamentos genéticos - Caldés, Trinidad (Psicooncología, 2005)
Genetic counseling plays a key role in the BRCA1/BRCA2 and hMLH1/hMSH2/hMSH6 testing process. The initial genetic counselling encounter will determine the appropriateness of the test by collecting a detailed family history and determining the likelihood that the family has a BRCA1/BRCA2, hMLH1/hMSH2/hMSH6 mutation. Once the test is offered, then genetic counselling discussions center around the possible test results, implications of the patient and other relatives, and risk and benefits of testing. The goal of this pre-test genetic counseling session is to ensure that patients have sufficient information with which to make a decision about being tested. At results disclosure, individuals can learn their results along with information about cancer risks and medical management options. Follow-up genetic counseling services can provide continued support and help arrange consultations with other medical care providers as needed. All clinical BRCA1/BRCA2; hMLH1/hMSH2/hMSH6 testing programs should include pre- and post-test genetic counseling.